A Child-Centred Research Checklist to Improve the Design and Reporting of Paediatric Research Studies: A Descriptive Mixed Methods Study - Foster, Mandie; Lisa Whitehead, L; O'Sullivan, Therese A; Hill, Julie; Mörelius, Evalotte (Elsevier BV, 2024)
Background No internationally developed child-centred research checklist is currently available to enhance the quality and transparency of the development, reporting and evaluation of research undertaken with children. Objective To develop an internationally relevant, expert informed child-centred research checklist. Design A descriptive mixed methods study was undertaken in five sequential phases, including a Delphi component. Setting(s) Academic/international context. Methods This study involved five sequential stages: 1. Literature review using four databases (CINAHL, MEDLINE, Scopus, PsycINFO) and analysis to identify key themes in child-centred research (January 2020). 2. Generate a questionnaire based on the key themes for international experts in child research to provide their opinions on what should be included in a child-centred research checklist (March 2020). 3. Inductive thematic analysis of the experts' responses to generate the initial draft checklist (June 2020). 4. The checklist progressed through three rounds of Delphi study for a wider range of experts to provide their consensus on what a child-centred research checklist should contain (August 2020–February 2021). 5. Refinement of the child-centred research checklist based on the Delphi study (March 2021–November 2022). Results A total of 160 articles met the inclusion criteria for review and were considered in the development of a 10-item open-ended questionnaire, adapted for four age-brackets (0-1 yrs., 2-4 yrs., 5-10 yrs., > 11 yrs). Responses from 14 experts across 10 countries generated 205 generic statements and 76 examples to inform a child-centred research checklist. Following this, 158 experts from eleven disciplines across 18 countries participated in the three round Delphi study (38 % retention rate over the three rounds). The final checklist includes 11 statements and 17 examples represented under three categories of “child-parent consent, assent and dissent”, “code of conduct” and “child focused methods”. Conclusion The child-centred research checklist was generated from a mixed methods study undertaken in five sequential phases, with input by 172 experts from 11 disciplines across 19 countries. The child-centred research checklist is the first international, expert informed tool to support good quality and transparent child-centred research. We call on researchers, clinicians, journal editors, organisations, and ethics committees to use this checklist for future research with children. The next phase of this project is engagement with children and their families to refine the checklist.
Keywords: 1110 Nursing; 4204 Midwifery; 4205 Nursing